Developing methods and tools for assessing flood damage on road infrastructure : a case study of Prey Veng Province, Cambodia - Chhoeurt, Sokla; Vilas Nitivattananon; Pramanik, Malay; Pal, Indrajit; AIT Scholarships and External Fund (Pathum Thani, Thailand : Asian Institute of Technology, 2024)
Due to the increased occurrence of flooding events in Cambodia, which poses a significant threat to the country's road infrastructure, that necessitating effective flood damage assessment methodologies. The lack of methodology for flood damage assessment on road infrastructure. Thus, this study aims to develop methods and tools for assessing flood damage on road infrastructure in Cambodia. The research employed a mixed-method approach, integrating various methodologies and techniques for evaluation, data collection, and analysis within case study to test results. This methodology combines both qualitative and quantitative research. The research included a thorough review of existing methods and tools, emphasizing direct flood damage at the river basin scale in Prey Veng. Spatial and statistical analysis methods were used, involving stakeholders to incorporate local knowledge and needs with data sources included government reports, satellite imagery, historical records, and field data collected through surveys and observations. The study employs a comprehensive approach, integrating spatial and statistical analyzes to assess flood damage to road infrastructure. Utilizing tools such as the Flood Water Depth Estimation Tool (FwDET), ArcGIS, QGIS, Google Earth Engine, OpenStreetMap, and Excel analysis, the research evaluates the impact of flood hazards on roads. The methodology includes risk assessment and depth-damage functions, enabling a thorough understanding of flood hazards and associated damage costs. The research, conducted at the river basin scale, highlights the economic impact of floods and provides insights into vulnerability zones, damage costs, and the relationship between flood hazard and damage values. Key findings underscore the significance of GIS tools and damage estimation curve in flood damage assessment, this contributes to cost-benefit analysis and informed decision-making for road development projects, recommending that future research employ these methodologies for effective adaptation costing and damage estimation in Cambodia's road infrastructure.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Innovation and Sustainability
Thesis (M. Sc.) - Asian Institute of Technology, 2024
Keywords: Flood damage -- Cambodia -- Case studies; Roads -- Cambodia -- Case studies